A survey of ESL teachers approaches to teaching reading in “Zon Besut Tengah”, Terengganu / Wan Azhan W. Nawang - W. Nawang, Wan Azhan (2002)
This survey is designed to explore the different methods and styles in teaching reading by ESL teachers in “Zon Besut Tengah”. The effective methods in teaching reading by ESL teachers will be closely observed and implemented with the aim to upgrade the standard of English performance in Besut especially among the rural schools. This hopefully will increase the level of reading proficiencies for students in “Zon Besot Tengah”. There were a total number of 35 ESL teachers from “Zon Besut Tengah’ involved and participated in this survey. A part from that, the key personnel from the Data Department, District Education Officers were also involved in this academic study. A total number of 35 or 100 % of the ESL teachers in “Zon Besut Tengah” perceived that they do not have enough knowledge or not well equipped for the latest in teaching information and developments of teaching methodologies. All the teachers in “Zon Besut Tengah” or 100 % agreed that they need to improved and upgraded their English level in tenns of Vocabulary, Grammar, Spelling and teaching methodologies. An impressive result showed that the teachers agreed on the teaching of pronunciation or phonetics should be looked and taught more often so that the students’ proficiencies in pronunciation would develop more.